PEMBUKAAN LAHAN PERKEBUNAN PERSPEKTIF UNDANG-UNDANG NOMOR 5 TAHUN 1960 TENTANG PERATURAN DASAR POKOK AGRARIA (STUDI TERHADAP PEMBUKAAN LAHAN PERKEBUNAN LADA DI DESA PASIRPUTIH, KECAMATAN TUKAK SADAI, KABUPATEN BANGKA SELATAN) - Darwance Darwance; Reko Dwi Salfutra; Yokotani Yokotani (Fakultas Hukum Universitas Bangka Belitung, 2018)
Most People around this country must have their own ways and mechanism for land issues before the form of written legislation is being publicized including people in Bangka Island. For example, the plantation land in Pasirputih Village, Tukak Sadai District, South Bangka Regency is arranged orderly. There are several requirements that must be obey in order to open the plantation land, such as they must be ‘herenteng’ (equal) between one plantation land and others. Besides, there are several prohibitions when opening the plantation land that shouldn’t be break by the people, those are ‘apit’ and ‘kaet’. These prohibitions are not written, but still being obeyed by the people. Something that is still maintained in this area is interesting to examine from the perspective of law number 5 of 1960 that is concerning the Basic Regulations of Agrarian (UUPA).